2020
DOI: 10.1136/gutjnl-2019-320273
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Barrett’s oesophagus through exhaled breath using an electronic nose device

Abstract: Timely detection of oesophageal adenocarcinoma (OAC) and even more so its precursor Barrett’s oesophagus (BO) could contribute to decrease OAC incidence and mortality. An accurate, minimally-invasive screening method for BO for widespread use is currently not available. In a proof-of-principle study in 402 patients, we developed and cross-validated a BO prediction model using volatile organic compounds (VOCs) analysis with an electronic nose device. This electronic nose was able to distinguish between patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 25 publications
2
35
2
Order By: Relevance
“…A recent study of Peters et al showed that Aeonose technology can detect a Barrett esophagus in patients with or without gastroesophageal reflux disease with a sensitivity of 91% and a specificity of 74%. In the future, the Aeonose might play an important role in the primary care setting as non-invasive screening for Barrett esophagus [26]. In the detection of tuberculosis, comparable Aeonose technology has shown its good diagnostic accuracy as well: a sensitivity of 93.5% and a specificity of 85.3% were found in distinguishing tuberculosis patients from healthy controls in Bangladesh [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of Peters et al showed that Aeonose technology can detect a Barrett esophagus in patients with or without gastroesophageal reflux disease with a sensitivity of 91% and a specificity of 74%. In the future, the Aeonose might play an important role in the primary care setting as non-invasive screening for Barrett esophagus [26]. In the detection of tuberculosis, comparable Aeonose technology has shown its good diagnostic accuracy as well: a sensitivity of 93.5% and a specificity of 85.3% were found in distinguishing tuberculosis patients from healthy controls in Bangladesh [30].…”
Section: Discussionmentioning
confidence: 99%
“…Since the diagnosis can be made within only sixteen minutes, the test can be considered a point-of-care test. Extensive research with the Aeonose has already been done not only in oncology [22][23][24][25] and pre-malignant disorders such as Barrett esophagus [26], but also into infectious diseases such as tuberculosis and in differentiating viral from bacterial respiratory infections in acute COPD exacerbations [27,28].…”
mentioning
confidence: 99%
“…Several approaches to overcome limitations of current screening policies have been explored to identify individuals at highest risk of BE and EAC. Recently, alternative screening modalities, such as transnasal endoscopy (TNE), nonendoscopic cell collection devices, and circulating and exhaled biomarkers, are being developed for the detection of BE to improve effectiveness, reduce costs, and minimize invasiveness of screening techniques compared with upper endoscopy ( 7 9 ). Although screening with these minimally invasive screening techniques is not yet recommended by current guidelines, various studies have piloted EAC screening with these techniques and have shown promising results ( 6 8 , 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of Peters et al showed that Aeonose technology can detect a Barrett esophagus in patients with or without gastroesophageal re ux disease with a sensitivity of 91% and a speci city of 74%. In the future, the Aeonose might play an important role in the primary care setting as non-invasive screening for Barrett esophagus (26). In the detection of tuberculosis, comparable Aeonose technology has shown its good diagnostic accuracy as well: a sensitivity of 93.5% and a speci city of 85.3% was found in distinguishing tuberculosis patients from healthy controls in Bangladesh (30).…”
Section: Discussionmentioning
confidence: 99%
“…Since the diagnosis can be made within only sixteen minutes, the test can be considered a point-of-care test. Extensive research with the Aeonose has already been done in oncology (22)(23)(24)(25) and pre-malignant disorders such as Barrett esophagus (26), but also into infectious diseases such as tuberculosis and in differentiating viral from bacterial respiratory infections in acute COPD exacerbations (27,28).…”
Section: Introductionmentioning
confidence: 99%